Wybory lokalne w Serbii. Spojrzenie krytyczne - Nastić, Maja (Studia Wyborcze, 2020)
In this essay, the author analyzes local elections as a type of electoral process in which citizens elect representatives in local assemblies. Although local elections have a long tradition, as does local self-government in Serbia, they cannot be viewed as a pillar of local community. The author’s starting point is that local elections are a “reflection of national elections”. The factors that contribute to this are: a proportional electoral system, a closed and blocked list of candidates, and the nature of the political representation of councillors, as well as the fact that local elections are never held separately from national elections.